The German, the Swiss and the US fiscal policy reaction to the financial crisis: comparing education and corporate policies from an adapted varieties of capitalism perspective - Hörisch, Felix; Weber, Jakob (Jahrbuch für Handlungs- und Entscheidungstheorie, 2017)
This paper looks at education and corporate coordination-policy outcomes within the fiscal stimulus packages of Germany, the USA, and Switzerland during the financial crisis of 2008/2009. The paper in
Gesehen am 01.08.2017